2019
DOI: 10.1186/s13287-019-1218-9
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells transplanted into spinal cord injury adopt immune cell-like characteristics

Abstract: Background Mesenchymal stem cells (MSCs) and their cellular response to various stimuli have been characterized in great detail in culture conditions. In contrast, the cellular response of MSCs in an in vivo setting is still uncharted territory. In this study, we investigated the cellular response of MSCs following transplantation into spinal cord injury (SCI). Methods Mouse bone marrow-derived MSCs were transplanted 24 h following severe contusion SCI in mice. As contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…It is known that the adult CNS, especially the injured CNS, may provide a relatively non-permissive environment for transplanted MSCs and other stem cells [43,53,54]. Even under the best circumstances, cell survival in injured CNS has been estimated to be less than 10% [43,55,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the adult CNS, especially the injured CNS, may provide a relatively non-permissive environment for transplanted MSCs and other stem cells [43,53,54]. Even under the best circumstances, cell survival in injured CNS has been estimated to be less than 10% [43,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…5). One of the most important reasons why those cells could not survive in the injured spinal cord for a long time is probably due to the sustained in ammation in the injury sites or the immediate in ammatory response elicited by surgery and injection manipulation [53,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies showed evidence that MSCs most likely act through their secretions (paracrine effect) [46][47][48] and not via their own integration/differentiation within the host tissue, some authors have reported the potential for MSCs transdifferentiation in cells of the nervous system and have shown that, after infusion into the spinal cord, these cells possibly promote regeneration of neurons because they have neuronal markers [49][50][51][52] . In vitro studies have shown that BM-MSC possess an intrinsic capacity to differentiate into neural-like and glial-like cells and express nestin, βIII-tubulin, neurofilaments, neuronspecific enolase, and glial fibrillary acidic protein (GFAP) [53][54][55] .…”
Section: Stromal Cells Therapymentioning
confidence: 99%
“…Thus, unique characteristics of MSCs derived from various tissues may have different therapeutic effects due to their unique characteristics. Although it is necessary to choose optimal MSCs for each central nervous system (CNS) disease and stage of illness, the timing of treatment with MSCs for SCI was mainly in the acute or subacute phase in previous studies [25][26][27]. In addition, relatively few reports have investigated differences in the therapeutic effects of MSCs derived from various tissued on chronic SCI.…”
Section: Introductionmentioning
confidence: 99%